The Future of Grounded Theory - Barney G. Glaser (Grounded Theory Review: An International Journal, 2022)
Editor’s Note: As we celebrate this great man’s life, we re-publish this gently edited paper about what the future of grounded theory is likely to be. Glaser discussed in whose hands the future of grounded theory appears to be as well as what accounts for its spread, its use, and its misuse. Glaser first wrote this paper in 1998 and updated it for publication in The Grounded Theory Review in 2010. Much of Glaser’s predictions have proven accurate.